Il dialetto nell’Italia postunitaria - Grochowska, Anna (Wydawnictwo Naukowe UAM, 2013)
Italian dialects occupy an important position in the history of Italian linguistics and are still present and relevant in the linguistic panorama of modern Italy. The purpose of this article is to outline the linguistic image of Italy by drawing attention to its dialects. Through analysis of the situation after unification in Italy in 1861, the author attempts to mark off functions and roles which dialects used to serve. In the second part of the article she concentrates on the phenomena of nuova dialettalità, or the new perspective and collocation of dialect in the Italian linguistic panorama of the 21st century. This article is a part of a research project dedicated to functions and uses of dialects in the Italian cinematography.
The dialect in Italy after the union
Keywords: dialect; national language; linguistic diversity; subculture; linguistic identity